Equilibrium Studies for Biosorbtion of Cr(III) by Roots of Calotropis procera - MUBEEN, HIFSA; NAEEM, ISMAT; TASKEEN, ABIDA; MUGHAL, TAHIRA (Asian Journal of Chemistry, 2010)
Chromium is present in different types of industrial effluents, being responsible for environmental pollution. Traditionally, the chromium removal is made by chemical precipitation. However, this method is not completely feasible to reduce the chromium concentration to levels as low as required by environmental legislation. Biosorption is a process in which solids of natural origin are employed for binding heavy metals. It is a promising alternative method to treat industrial effluents, mainly because of its low cost and high metal binding capacity. The aim of the present study is to utilize the locally available wild plant material for heavy metal removal from industrial wastewater. The wastewater containing trivalent chromium was treated with biomass prepared from roots of Calotropis procera. These studies were carried out in order to determine some operational parameters of chromium sorption such as the time required for the metal-biosorbent equilibrium, the effects of change in biomass quantity and pH. It was found that a time of 50 min is sufficient enough to attain equilibrium. The optimum pH was found to be 4 for chromium. The biosorption data was well fitted to Langmuir and freundlich adsorption model. It is concluded that adsorbent prepared from Calotropis procera roots can be used for treatment of heavy metals in waste waters.